2018
DOI: 10.1016/j.ijdrr.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Language translation during disaster: A comparative analysis of five national approaches

Abstract: Clear, timely and accurate information is recognised as strategically and operationally critical to disaster response effectiveness. Increasing cultural and linguistic diversity across the globe creates a demand for information to be available in multiple languages. This signifies a need for language translation to be a key element of disaster management. However, language translation is an underdeveloped tool in disaster management and has been a neglected topic in research. We analyse the disaster response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 21 publications
(16 reference statements)
1
51
0
1
Order By: Relevance
“…feedback about services or information about people who have been injured or require help) and for coordination of aid providers. Access to information has been described as a right of populations affected by crisis (see, O'Brien et al, 2018). It has also been suggested that information constitutes a basic humanitarian good alongside food, water, shelter and healthcare (Greenwood et al, 2017).…”
Section: Language and Exclusion In Humanitarian Crisismentioning
confidence: 99%
“…feedback about services or information about people who have been injured or require help) and for coordination of aid providers. Access to information has been described as a right of populations affected by crisis (see, O'Brien et al, 2018). It has also been suggested that information constitutes a basic humanitarian good alongside food, water, shelter and healthcare (Greenwood et al, 2017).…”
Section: Language and Exclusion In Humanitarian Crisismentioning
confidence: 99%
“…Increasing cultural and linguistic diversity across the globe intensifies the complexity of the communicative situation, and communicating appropriately is recognised as a complex process fraught with challenges that results in significant negative impacts if not addressed (Arlikatti et al, 2014;Henry et al, 2011;Nepal et al, 2012). Ground-breaking scholarship focusing on interpreting in crises (Bulut and Kurultay, 2001;Moser-Mercer et al, 2014;Tipton, 2011) and translation in crises (Federici, 2016;Federici and Cadwell, 2018;O'Brien et al, 2018) has begun to address some of these challenges. Nevertheless, many more questions remain to be answered.…”
Section: Defining and Delimiting Trust Distrust Translationmentioning
confidence: 99%
“…O'Brien [ 13 ] noted that while the crisis communication literature is gaining increased recognition of the importance of language translation and cross-cultural communication, there is still a lack of in-depth studies focusing on the translation experience and the associated implications for crisis communication. In another study, the authors described the translation of emergency information as an underexplored or neglected research topic [ 14 ]. They analysed the disaster response approaches for five countries, namely New Zealand, Ireland, the UK, Japan and the USA, and found different levels of inadequacies in the use of language translation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the authors described the translation of emergency information as an underexplored or neglected research topic [ 14 ]. They analysed the disaster response approaches for five countries, namely New Zealand, Ireland, the UK, Japan and the USA, and found different levels of inadequacies in the use of language translation [ 14 ]. In a more recent article, the need for increased attention to the translation of emergency information was again highlighted, with a recommendation that this be included in emergency planning and preparation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%